Patterns of connectivity were different depending on time alignment. - Adam J. O. Dede (11554007) (2025)
In panels A-D, the Y axes display the proportion of the time-frequency space for all tested connections that exhibited a significant difference between hit and miss trials after permutation-based cluster correction. A. The x-axis displays frequency. B. The x-axis displays time relative to HFB peak. C. As A for image-locked analysis. D. The x-axis displays time relative to image onset. Panels A,B,C, and D can be regenerated using data contained in HFBConnections.mat and imageConnections.mat and code in Figure4ABCD.m [112]. E. The connection schematics display connections that were significantly increased for hit relative to miss trials for HFB-locked analysis. Line colors indicate the region whose HFB peak was used for temporal alignment. The rows display those connections that exhibited significance before (top), during (middle), and after (bottom) the HFB peak. The columns correspond to encoding (left) and retrieval (right). Dots represent color-coded region locations. The thickness of lines connecting dots represents the t-value of the difference between hit and miss trial connectivity. Connections between pairs of channels within a single ROI are represented with self-referencing loops. F. Line colors indicate the mean frequency of the significant difference between hit and miss trials. The connection schematics reflect mnemonic connections from the image-locked analysis. All other conventions are similar to E except that time is divided into peri-stimulus (top), mid-trial (middle), and late-trial (bottom) periods. Panels E and F can be regenerated using data contained in HFBConnections.mat and imageConnections.mat and code in Figure4EF.m [112]. For hit less than miss differences, see S7 Fig.